How are patterned movements stored in working memory? - Li, Congchong; Tian, Wenqing; He, Yang; Wang, Chaoxian; Wang, Xianyang; Xu, Xiang; Bai, Lifeng; Xue, Ting; Liao, Yang; Xu, Tao; Liu, Xufeng; Wu, Shengjun (Frontiers in Psychology, 2023)
Introduction In this study, the change detection paradigm was used to study the working memory of patterned movements and the relationship of this type of memory with the visuospatial sketchpad in three experiments. Methods Experiment 1 measured participants’ working memory capacity for patterned movements and explored the influence of stimulus type with indicators such as response time and accuracy rate. Experiments 2 and 3 explored the relationship between patterned movements and the visual and spatial subsystems, respectively. Results The results of Experiment 1 indicated that individuals can store 3–4 patterned movements in working memory; however, a change in stimulus format or an increase in memory load may decrease the speed and efficiency of working memory processing. The results of Experiment 2 showed that working memory and visual working memory are independent when processing patterned movements. The results of Experiment 3 showed that the working memory of patterned movements was affected by spatial working memory. Discussion Changes in stimulus type and memory load exerted different effects on the working memory capacity of participants. These results provide behavioral evidence that the storage of patterned movement information is independent of the visual subsystem but requires the spatial subsystem of the visuospatial sketchpad.